Las precisiones para la enseñanza y el aprendizaje en el desarrollo del bloque geométrico en los estudiantes de octavo año de Educación General Básica de la unidad Educativa “Leonardo Murialdo” del cantón Archidona, Provincia de Napo, en el período académico 2014-2015 - Chuiza Román, Héctor Oswaldo (2016)
In the learning process of the block of geometry there are many difficulties, especially with an exact science and this can complicate the students' academic process, and this makes them to feel discouraged and lose interest in learning the subject. As teacher of the Education Unit "Leonardo Murialdo", due to concern of Parents, students are committed to overcome this problem, looking for a suitable mechanism that allows them to learn geometry1. This research aims to demonstrate that from the details for teaching and learning, an attitude change was achieved and therefore a significant interest in the development of geometric block by eighth grade students, which was verified based on the results obtained. In the process of research it was determined: the members of the process, the methodological strategies and teaching resources; it was developed and implemented the alternative proposal, based on the process of teaching and learning, pedagogy and information processing. To demonstrate statistical hypothesis t-student test was applied between the studies of the variables by applying the Guide "To play with geometry". After the application, the students presented interest, active participation individually and in groups; it concluded that the clarifications of the teaching learning are developed in the geometric block, it is important to note that there was collaboration and approval of the members that arc part of the research.